Notes on the Natural History of Helicops leopardinus (SCHLEGEL, 1837) (Serpentes: Hydropsini) in a large urban center - Rodrigues de Sousa, Átilas; Feitosa Quirino, Tatiana; Franklin Fernandes de Carvalho, Elvis; Oliveira Arruda, Mariny (Herpetologia Brasileira, 2026)
Urban centers represent emerging socio‑ecological ecosystems that promote novel interactions, behavioral changes, and, consequently, new evolutionary trajectories. Population projections indicate that more than 60% of the world’s population will be living in urban areas by 2030, leading to habitat reduction and loss of space for wildlife. In this study, we investigated the diet and parasite ecology of an urban population of the water snake Helicops leopardinus. To this end, 50 individuals from scientific collections were analyzed. We recorded the first case of H. leopardinus consuming Nile tilapia (Oreochromis niloticus), which accounted for 50% of the total prey volume recorded. In addition, we documented the presence of cestode parasites of the genus Ophiotaenia, infecting 16% of the sampled individuals. These findings highlight the ecological flexibility of the species and contribute to a better understanding of wildlife responses to urban environments.